Misbehaviour no trabalho: a dimensão encoberta da vida organizacional - Pessoa, Deborah Kelly Nascimento (2017)
This thesis aims to analyze how misbehavior happens in the organization backstage. The literature helps to define misbehavior as incompatible or counterproductive practices (ACKROYD; THOMPSON, 1999), “activities occurring with the workplace that according to the oficial structure, culture and rules of the organization, ‘should not happen’, and contain na element of challenge to the dominant modes of operating to dominant interest in the organization” (WATSON, 2003, p. 230), “misbehaviour is not just about employee resistance; it is about dealing with the pressures of work in a less opposing manner. Misbehaviour is about conflicts that cannot be exclusively attributable to the effort-bargain relationship between employer and employee” (RICHARDS, 2007, p. 35-36). To achieve the research objectives, we guide the study in the qualitative approach, studing a company that operates as bakery, cafe and restaurant. Ethnography was choosed as research strategy by allowing capture the minutiae of the researched context in an intense relationship of exchange with the study object. Inductive behavior to the fieldwork was adopted as research guidance, this fieldwork lasted approximately 10 months and produced 657 pages of field diary. The research analysis and theoretical construction was conducted according to the grounded theory approach, using Straus and Corbin (2008) as a guiding to the categorization process. The categories was organized according to the Gioia, Corley and Hamilton (2012) work. Numerous misbehavior actions was identified, for example: eating food products and raw materials in the company, non-compliance with working hours and safety standards, sabotage of sales, rude treatment of consumers, gossip, aggressive, snobbish or prejudice behavior against coworkers, theft of raw materials and confidential recipes, and so forth. As result, this study concludes indicating that misbehaviour is a kind of resistance that goes beyond organizational boundaries and the opposition relationship against management, misbehaviour is influenced by individual, organizational and social dimensions.